УЛС ТӨРИЙН НАМУУДЫН НИЙГЭМ – УЛС ТӨРИЙН ХАРИЛЦААН ДАХЬ ҮҮРЭГ, ТҮҮНИЙ ЭРХ ЗҮЙН ҮНДЭС - С.ЗҮЛЬФИКАР (Politology, 2023)
Although political parties are defined by a central function (the filling of political office and wielding of government power), their impact on the political system is substantially broader and more complex. A number of general functions of parties can nevertheless be defined. The main functions are as follows: organizational right for declaring and implementing social and political right, representation; power holding, interest articulation,elite formulation. These functions are clearly defined relevant law and legal documents as in both national legal system and party legal relations. Parties draw together people who have similar political and social philosophies and ideasRepresentation is often seen as the primary functions of parties. It refers to the capacity of parties to respond and articulate the views of both members and the voters. Parties of all kinds are responsible for providing states with their political leaders. In most cases, parties therefore provide a training ground for politicians, and equipping them with skills, knowledge and experience, and offering them some form of career structure. In the process of developing collective goals, parties also help to articulate and aggregate the various interests found in society. The fact that national parties invariably articulate the demands of a multitude of groups forces them to aggregate these interests by drawing then together into a coherent whole, balancing competing interests against each other. Final goal for political parties is defined by competing for the government or state power. Parties are the chief means by which political power is exercised inMongolia. Parties help with formation of governments, in parliamentary systems to the extent that is possible to talk of “party government”.